2021
DOI: 10.1111/imig.12839
|View full text |Cite
|
Sign up to set email alerts
|

Colombia's open‐door policy: An innovative approach to displacement?

Abstract: Colombia is host to one of the largest forced migration flows in the world, having received at least 1.7 million Venezuelans, most since 2015, as political conflict in Venezuela increased, the economy imploded, and the state abdicated many of its basic functions. An additional half million Colombian nationals who were living in Venezuela moved back to Colombia over the same period. Overall, more than 5.4 million Venezuelans have abandoned their country, with more than 4.6 million of them staying in Latin Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…For example, Colombia and Peru, have received more than 1.8 million Venezuelan immigrants and refugees, thus implementing massive regularization campaigns to grant them temporary legal status (Seele, 2019). In a report by the Migration Policy Institute, Selee et al (2019) argue that countries such as Colombia, Peru, Ecuador, Argentina, Chile, Brazil, Panamá, and Mexico developed creative solutions to face the Venezuelan migratory crisis. Some examples are new legal permits (i.e., Special Stay Permit in Colombia, Temporary Stay Permit in Perú, and the Democratic Responsibility Visa in Chile), regularization programs (i.e., Administrative Registry of Venezuelan Migrants in Colombia), and expanding the use of existing visas (i.e., UNASUR visa in Ecuador).…”
Section: A Changing Regional Landscapementioning
confidence: 99%
“…For example, Colombia and Peru, have received more than 1.8 million Venezuelan immigrants and refugees, thus implementing massive regularization campaigns to grant them temporary legal status (Seele, 2019). In a report by the Migration Policy Institute, Selee et al (2019) argue that countries such as Colombia, Peru, Ecuador, Argentina, Chile, Brazil, Panamá, and Mexico developed creative solutions to face the Venezuelan migratory crisis. Some examples are new legal permits (i.e., Special Stay Permit in Colombia, Temporary Stay Permit in Perú, and the Democratic Responsibility Visa in Chile), regularization programs (i.e., Administrative Registry of Venezuelan Migrants in Colombia), and expanding the use of existing visas (i.e., UNASUR visa in Ecuador).…”
Section: A Changing Regional Landscapementioning
confidence: 99%
“…UN High Commissioner for Refugees Filippo Grandi welcomed the announcement by President Ivan Duque as a humanitarian example for the region (Grandi, 2021). Research has shown that Venezuelans who are recognized in Colombia have been able to find a degree of inclusion in Colombia and some level of access to services (Selee & Bolter, 2021). It may be possible that extending the residency period to 10 years could help support inclusion by reducing liminal factors that impede Venezuelans.…”
Section: Colombiamentioning
confidence: 99%
“…1 Despite evidence that around 85 percent of refugees and people in need of international protection live in developing nations, most research on the legislative frameworks for the protection of refugees has focused on OECD countries (Bjerre et al 2015; Helbling et al 2017; Helbling and Kalkum 2018). Until the Venezuelan displacement crisis in 2015, Latin America was one of the least-researched regions in the field of refugee studies, likely because of its low refugee numbers, compared to other regions such as the Middle East or East Africa (Pugh 2018; International Crisis Group 2018; UNHCR 2018; Freier and Holloway 2019; Freier and Parent 2019; Selee et al 2019). However, in Latin America, scholars have claimed, a new liberal turn in asylum policies has taken place as part of an overall liberalization of migration policies in the region (Ceriani 2011; Acosta and Freier 2015; Cantor, Freier, and Gauci 2015; Ceriani and Freier 2015; Freier 2015; Fernandez-Rodriguez, Freier, and Hammoud-Gallego 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This tradition has been concretely reinforced since 1984, when the informal process that kickstarted the development of a regional refugee protection framework in Latin America began (De Andrade 2014; Barichello 2016). Second, Latin America is currently experiencing its most significant displacement of people across the region since the Central American crisis of the 1980s (International Crisis Group 2018; Acosta, Blouin, and Freier 2019; Selee et al 2019; Berganza, Blouin, and Freier 2020; Chavez Gonzales and Estrada 2020; Selee and Bolter 2020). Due to the deteriorating economic and political situation in Venezuela, the UNHCR estimates that in recent years, 4.5 million people have left the country (UNHCR 2020), a significant number for a country that until recently had a long history of attracting migrants from other parts of Latin America (International Crisis Group 2018; Bahar and Dooley 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation